A paródia bíblica em Galiléia de Ronaldo Correia de Brito - Ribeiro, Elizabeth Francischetto (2011)
This research, when select Galiléia (2008), by Ronaldo Correia de Brito, was aimed to main study the biblical parody employed by the author in the aesthetic transfiguration of the interior reality. Thereby was could analyze that when author gives a new context to the Bible, the parody configures itself in this creative approach to the past text. Brito rewrites the biblical text with a new perspective on events. The intent of parody in Galiléia was not ridiculing the Bible, but use it as a model by which places the contemporary interior at focus. The analysis of the parody allowed the reflection and understanding to the writing. By appropriation textual, the novel of the Brito showed his self-consciousness ficcional and self-reflexivity. The argumentation of the parody was based on the presuppositions espoused by Linda Hutcheon that drafted its own theory that characterizes all modern art. They are also in agreement with the poetics of postmodernism of the Linda Hutcheon, complemented to the thinking of other theorists such as Fredric Jameson, Jean Francois Lyotard, Stuart Hall, and Roland Barthes, the analysis of the literary criticism of this study.